A Stackable Triboelectric Nanogenerator for Wave-Driven Marine Buoys - Hao Wang; Chuanqing Zhu; Weichen Wang; Ruijiang Xu; Pengfei Chen; Taili Du; Tingxi Xue; Zhaoyang Wang; Minyi Xu (Nanomaterials, 2022)
Marine distributed devices are essential infrastructure for exploring and utilizing the ocean. As the most common carrier of these devices, floating and submerged buoys are subject to a bottleneck of power supply. Recent progress in nanogenerators could convert the high-entropy marine kinetic energy (e.g., wave) robustly, which may form an in-situ power solution to marine distributed devices. This study is devoted to develop a stackable triboelectric nanogenerator (S-TENG), while each layer of it is made into multiple channels carrying PTFE balls in between Aluminum electrodes. In the experiments based on forced motion, the peak power density of the S-TENG reaches 49 W/m3, about 29% promotion from our previous benchmark. The S-TENG has also become less vulnerable to directional variation of the excitation, making its integration on various platforms more flexible in real conditions. In practice, the S-TENG has demonstrated its capability of powering LEDs as well as various sensors measuring salinity, temperature and acidity, which means the S-TENG could self-power many compact marine buoys.